Anxiety, depression and post-traumatic stress in nursing professionals during the covid-19 pandemic, in the northern zone of Ecuador, 2022 (Horizontes de Enfermería, 2023)
At present, there is a growing interest in addressing the impact of the COVID-19 pandemic on nursing staff. The prevalence of anxiety, depression, and the presence of post-traumatic syndrome in nursing professionals in the province of Carchi was investigated; through a descriptive cross-sectional study in a random sample of 229 nursing professionals. A survey was used that contains sociodemographic variables, the Hospital Anxiety and Depression scales (HADS), and the stressor impact scale (IES-R); the Pearson bivariate correlation test was used with a significance level of p
Keywords: Anxiety; covid-19; depression; nursing; burnout syndrome; post-traumatic stress disorders